The International Status of Taiwan in the New World Order: Legal and Political Considerations - Henckaerts, Jean-Marie, (International Law - Book Archive pre-2000., 1996)
This book examines the most important issues determining the international status of Taiwan today: its international legal status, the viability of its flexible democracy, its efforts to gain participation or membership in international organizations, most notably the United Nations, and its future relations with mainland China, ranging from reunification to declared independence. Issues of American and European foreign policy and of domestic Chinese and Taiwanese politics are also addressed where relevant. This book is unique in that it looks at the question of Taiwan from the perspective of both international law and politics as it confronts the imperatives of law and the limitations of real world politics. As a result it offers insights and strategies that are both sensible and feasible. This book is aimed at scholars and practitioners of international law and international relations alike.